ANALISIS STRATEGI PEMBANGUNAN DAERAH BERDASARKAN APBD DI KOTA BUKITTINGGI TAHUN 2024 - Sendika, May; Asnil; Aldri Frinaldi; Nora Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the regional development strategy of Bukittinggi City based on the Regional Revenue and Expenditure Budget (APBD) for 2024 and its budget allocation changes. The main problem of the research is how APBD changes reflect development priorities and their implications for the regional economy. This study employs a quantitative descriptive method with financial ratio analysis and comparative evaluation between the budget before and after amendments. Secondary data was obtained from official documents of the Amended Regional Budget Regulation for Fiscal Year 2024 of Bukittinggi City. The research findings indicate an increase in regional revenue of IDR 17.42 billion (2.30%), primarily from intergovernmental transfers which increased by IDR 19.17 billion (56.90%). Capital expenditure experienced a significant increase of IDR 3.36 billion (5.00%), particularly in road, network, and irrigation spending which increased by 86.52%. These findings indicate that the Bukittinggi City Government prioritizes infrastructure development as the main strategy to enhance connectivity and regional economic growth, consistent with regional development theory emphasizing the importance of capital investment in stimulating long-term economic growth.